MEDICINAL INTEREST OF AZO-BASED ORGANIC COMPOUNDS: A REVIEW - Sahoo, Jyotirmaya; Paidesetty, Sudhir Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT The azo derived products are versatile building blocker organic compounds used in drug research. In this review, we include the synthetic strategy and medicinal utility of some new azo derived candidates in recent years, which must be a good source of information to the researchers. A number of research articles explored with the help of different electronic databases such as PubMed, Scopus, Science direct, Crossref, Orcid, and Google Scholar to study the various biological activities of azo compounds. A number of journals from last decades were surveyed and found to be observed that azo-linkage synthetic organic compounds have good therapeutic properties, viz., antitumor, antioxidant, antiviral, antimicrobial, antidiabetic, anticonvulsant, and antidepressant activity. Keeping the medicinal utility included in the article, it can be concluded that the invention of new azo molecules and their complexes should be encouraged to present novel bioactive molecules. Keywords: Diazotization, Antioxidant, Cytotoxic, Cholinesterase, Antitubercular.